Teacher’s Communication Strategies for Enhancing Students’ Speaking Motivation: Verbal and Non-Verbal - Andi Adisaturrahimi; Sabrina Retnasari Iswahyudi; Fitri Amaliah Akbal; Marlia Marlia; Muhammad Astrianto Setiadi (AT-TA'LIM, 2025)
This study investigated the impact of teacher’s verbal and non-verbal communication strategies on students’ motivation to speak in English. Specifically, it explored the types of verbal and non-verbal communication strategies employed by the teacher and examined how these strategies influence students’ speaking motivation in the EFL context.  A qualitative method was adopted, focusing on ninth-grade students at SMPN 1 Pallangga during the 2022–2023 academic year. Data were collected through classroom observations and semi-structured interviews. The results indicated that the teacher employed 13 distinct of verbal strategies and eight forms of non-verbal communication strategies. The findings suggested that both verbal and non-verbal communication strategies positively contribute to enhancing students' motivation to speak in English, highlighting the importance of teacher-student interaction in EFL classrooms.